Respuesta :

Answer:

(6-u)/(6-7)= (6-u)/-1= 8

6 - u = -8

-u = -14

u = 14

Answer:u = - 2

Step-by-step explanation:

Slope = change in value of y on the vertical axis / change in value of x on the horizontal axis

change in the value of y = y2 - y1

Change in value of x = x2 -x1

y2 = final value of y

y 1 = initial value of y

x2 = final value of x

x1 = initial value of x

From the information given,

Slope = - 8

y2 = 6

y1 = u

x2 = 6

x1 = 7

Therefore,

- 8 = (6 - u)/(6 - 7)

- 8 = (6 - u)/ - 1

6 - u = 8

u = 6 - 8 = - 2

ACCESS MORE